Strengthening Students' Islamic Character Education through Ecopedagogic-Based Learning; Case Study at Darul Huffadz Primary School - Dodi Kurniawan; Slamet Firdaus; Ilman Nafia; Septi Gumiandari (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractThe increasing neglect of moral and character education in the era of digitalization highlights the urgent need for ecopedagogy as a transformative approach to foster ecological awareness and prevent environmental degradation. This research aims to determine (1) the concept of ecopedagogics in natural school-based Islamic character education; (2) the application of ecopedagogic-based learning models at Daarul Huffadz Primary School; and (3) the implications of ecopedagogics in strengthening natural school-based Islamic character education at Daarul Huffadz Primary School. This research uses a qualitative analytical descriptive approach. Data was obtained through interview techniques with 7 school administrators, observation of learning activities in class III, totaling 28 students, and documentation studies through the Lesson Plan and intra-school student organization syllabus as comparison material with other formal schools. The research results found (1) the ecopedagogic concept in Islamic character education is applied using the concept of learning with nature referring to three core curricula and four basic foundations, namely moral, leadership, scientific logic, and entrepreneurship developments; (2) the implementation of learning refers more to the achievement of development and character formation of students which is determined through attitudinal or affective assessments; (3) the development of ecopedagogical education as character education has eight main character pillars as a reference for student outcomes. These findings highlight that ecopedagogic education integrates environmental awareness with character development, providing a holistic approach that shapes students into responsible, ethical, and environmentally conscious individuals.Keywords: ecopedagogic, Islamic character education, natural school. AbstrakMeningkatnya pengabaian pendidikan moral dan karakter di era digitalisasi menyoroti kebutuhan mendesak akan ekopedagogi sebagai pendekatan transformatif untuk menumbuhkan kesadaran ekologis dan mencegah degradasi lingkungan. Penelitian ini bertujuan untuk mengetahui (1) konsep ekopedagogi dalam pendidikan karakter Islam berbasis sekolah alam; (2) penerapan model pembelajaran berbasis ekopedagogi di Sekolah Dasar Daarul Huffadz; dan (3) implikasi ekopedagogi dalam penguatan pendidikan karakter Islam berbasis sekolah alam di Sekolah Dasar Daarul Huffadz. Penelitian ini menggunakan pendekatan deskriptif analitis kualitatif. Data diperoleh melalui teknik wawancara dengan 7 administrator sekolah, observasi aktivitas pembelajaran di kelas III yang berjumlah 28 siswa, dan studi dokumentasi melalui Rencana Pelaksanaan Pembelajaran dan silabus organisasi siswa intra sekolah sebagai bahan perbandingan dengan sekolah formal lainnya. Hasil penelitian menemukan (1) konsep ekopedagogi dalam pendidikan karakter Islam diterapkan menggunakan konsep belajar dengan alam mengacu pada tiga kurikulum inti dan empat landasan dasar, yaitu pengembangan moral, kepemimpinan, logika ilmiah, dan kewirausahaan; (2) pelaksanaan pembelajaran lebih mengacu pada pencapaian pengembangan dan pembentukan karakter peserta didik yang ditentukan melalui penilaian sikap atau afektif; (3) pengembangan pendidikan ekopedagogi sebagai pendidikan karakter memiliki delapan pilar karakter utama sebagai acuan capaian peserta didik. Temuan ini menyoroti bahwa pendidikan ekopedagogi mengintegrasikan kesadaran lingkungan dengan pengembangan karakter, memberikan pendekatan holistik yang membentuk peserta didik menjadi individu yang bertanggung jawab, beretika, dan sadar lingkungan.Kata kunci: ecopedagogic, pendidikan karakter Islam, sekolah alam.